ANALISIS LAPORAN KEUANGAN LABA RUGI PADA USAHA TERNAK KAMBING PERANAKAN ETAWA ARDITA FARM PACITAN - Yuhana, Happy; Mustoffa, Ardyan Firdausi (Universitas Muhammadiyah Tangerang, 2024)
This research was conducted at the Etawa Ardita Farm Pacitan Peranakan goat farming business which is located at Ringinasri, Tegalombo District, Pacitan Regency. This research aims to find out how to record financial reports, find out how to prepare business financial reports according to SAK EMKM and analyze profit and loss reports for businesses Etawa Ardita Farm crossbreed goat farming, Pacitan district. The theories used in this research are theories about profit and loss financial statements which relate to company profits and losses. The method used in this research is a quantitative method. The data from this research is profit and loss financial report data from 2021-2023 in the Peranakan goat farming business Etawa Ardita Farm Pacitan. Data analysis in this study used horizontal analysis. From the results of the analysis that has been carried out, the development of the profit and loss report for the Etawa Ardita Farm Pacitan Peranakan goat farming business. In 2021 – 2022 net income has increased (3%), in 2022 – 2023 net income has decreased (13%). The factors causing the decline in net profit in 2023 in the Etawa Ardita Farm Peranakan goat farming business are the increase in costs caused by feed costs which increased 50% from an index figure of 100% to 150% and increased 40% compared to 2022, the cost of medicines an increase of 20% from the index figure of 100% to 120% and an increase of 20% from the previous year, as well as additional salary costs of IDR 24,000,000, where in the previous year there were no salary costs.